Peran Manajerial dan Teknisi Humas Lembaga Pemerintah dan Swasta - Rachmat Kriyantono (Universitas Muhammadiyah Ponorogo, 2018)
The research aims to describe the implementation level of managerial and technician roles of public relations practitioners from government and private institutions in Indonesia. The hypothesis is public relations from private institutions often more apply the managerial roles while the practitioners from government public relations tend to apply technical communication than managerial roles of communication. The researcher uses positivistic paradigm by applying survey method with questioners which are filled by 105 respondents. The instrument are from Five-Factor Dimension Model that specifically measures the level of managerial and technician roles of communication. The research finds that there is no significant differentiation between public relations practitioners from government and private institutions regarding the dimensions of managerial and technician roles. Both practitioners frequently apply technician roles rather than managerial roles, however, the government public relations more frequently conduct managerial roles than practitioners from private institutions. The research contributes to the development of public relations study and practice in Indonesia by testing the managerial and technical roles conducting by public relations practitioners through using Five-factor Model.